A study on catching freshwater crayfish, Astacus leptodactylus Eschscholtz 1823, and its some population characteristics - Dartay, Mürşide; Ateşşahin, Tuncay (My University, 2013)
This study was carried out between July 2009 and March 2010, which is the first scientific survey on catching freshwater crayfish in the Keban Dam Lake Pertek region (38°49'271" N - 39°17'057" E), Catch per unit effort (CPUE) was 0.2 number/fyke net/number of trial. The most efficiently catching was in November (20 crayfish) and the least efficiently catching was in March (4 crayfish). The catching depth was between 3 and 16 meters. The sex ratio was 0.42/1 (female/male). The mean total length for males and females were 112.93 mm and 100.38 mm, respectively. The mean weight for males was 50.32 ± 4.34 g, for females was 35.82 ± 5.76. The legal length for freshwater crayfish is 100 mm. In this study was determined 76.6 % of samples total length higher than 100 mm, 23.4 % of samples total length lower than 100 mm. Caught crayfish had a linear relationship between carapace length and total weight in both gender (r2male=0.946, r2female= 0.704). According to the regression analysis, male crayfish had a positive allometric growth, females had a negative allometric growth (bmale=3.018, bfemale=2.338). It was determined that abdomen of females was statistically wider than male’s abdomen (p<0.05). On the other hand, chelae width and chelae length for males were statistically higher than females (p<0.05). It can be said that population of crayfish in the region is not sufficient for commercially catching; however, it will be able to supply an important economic benefit by getting increase in the future.

Kerevit (Astacus leptodactylus) avcılığı üzerine ilk bilimsel çalışma özelliğini taşıyan bu araştırma, Temmuz 2009 - Mart 2010 tarihleri arasında Keban Baraj Gölü Pertek Bölgesi’nde gerçekleştirildi (38°49'271" N - 39°17'057" E). Birim çabadaki av miktarı (CPUE) 0,2 adet kerevit/pinter/deneme sayısı olarak hesaplandı. En verimli avcılık Kasım ayında (20 adet), en az avcılık Mart ayında(4 adet) gerçekleşti. Pinterler 3-16 m arasındaki derinliklere atıldı. Populasyondaki dişi / erkek oranı 0,42/1,00 olarak belirlendi. Kerevitlerin ortalama boyları erkek kerevitlerde 112,93 ve dişi kerevitlerde 100,38 olarak saptandı. Erkek kerevitlerin ortalama ağırlığının 50.32 ± 4.34 g, dişilerin ortalama ağırlığının ise 35.82 ± 5.76 g olduğu tespit edildi. Avlanabilir boydaki ( ? 10 cm) bireylerin oranı % 76.6, 100 mm’nin altındaki bireylerin oranı % 23.4 olarak hesaplandı. Avlanan erkek ve dişi kerevitlerde (Astacus leptodactylus) karapaks uzunluğu ile vücut ağırlığı arasında doğrusal bir ilişkinin olduğu (r² erkekler= 0.946 ve r² dişiler= 0.704) saptandı. Bununla birlikte, regrasyon analizlerinden erkek kerevitlerde pozitif allometrik bir büyümeyi, dişilerde ise negatif allometrik bir büyümenin olduğu tespit edildi (eğim erkekler= 3,018 ve eğim dişiler= 2,338). Dişilerin erkeklere göre abdomenlerinin istatistiksel olarak önemli derecede geniş olduğu (P < 0.05), erkeklerin ise dişilere göre kıskaç genişliğinin ve kıskaç ile kıskaç ayaklarının istatistiksel olarak önemli derecede uzun olduğu saptandı (P <0.05). Sonuç olarak, A. leptodactylus türü kerevitlerin bu bölgede zaman içerisinde populasyonlarındaki artışla birlikte ülke ve yöre ekonomisine katkıda bulunacağı düşünülmektedir.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Astacus leptodactylus; Catching crayfish; Fyke Net; Pertek Region; Kerevit avcılığı; Pinter; Pertek Bölgesi